How Do the Skilled and the Unskilled Respond to Regional Shocks? : The Case of Spain - Mauro, Paolo (IMF Working Papers; Working Paper, 1998)
Are there any differences in how workers of different skill levels respond to regional shocks? This paper addresses that question using the methodology of Blanchard and Katz (1992) and a unique data set on working-age population, labor force, and employment for five educational groups (ranging from the illiterate to the college-educated) over 1964-92 for the 50 Spanish provinces. The paper finds that the high-skilled migrate very promptly in response to a decline in regional labor demand, while the low-skilled drop out of the labor force or stay unemployed.